(untitled) - Graves, Philip E (Boca Rato, 2014)
This is the Preface to Environmental Economics: An Integrated Approach, and it provides a description of the approach taken throughout the book. The approach is to first understand how environmental policy would be conducted in a world of "perfect information," then move on to sources of difficulty in acquiring the necessary information, and continuing to the various methodologies employed by environmental economics to gain valuation insights.
Keywords: Environmental economics,Kinh tế môi trường